Translation of addictions science into practice - Miller, Peter M. (Peter Michael), 1942-; Kavanagh, David John. (Boston, Mass. : Pergamon, 2007)
From basic research to improved clinical practice and social policy.
Front cover; Translation of Addictions Science into Practice; Copyright page; Table of Contents; List of Contributors; Preface; Section I: Genetics and Neuroscience; Section II: Pharmacotherapy; Section III: Psychology and Sociology; Section IV: Practice and Policy; Section V: Conclusion; Subject Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Drug abuse -- Physiological aspects; Substance abuse -- Physiological aspects; Drug abuse -- Treatment; Substance abuse -- Treatment; Toxicomanie -- Aspect physiologique; Polytoxicomanie -- Aspect physiologique; Toxicomanie -- Traitement; Abus de substances psychoactives -- Traitement; SELF-HELP -- Substance Abuse & Addictions -- General; SELF-HELP -- Substance Abuse & Addictions -- Drug Dependence; SELF-HELP -- Twelve-Step Programs; Drug abuse -- Physiological aspects; Drug abuse -- Treatment; Substance abuse -- Physiological aspects; Substance abuse -- Treatment